Evolution of IFN-γ response against mycobacterial antigens used for the diagnosis of bovine tuberculosis in BCG vaccinated cattle under a natural transmission setting in central Chile - Benavides, María B.; Ábalosa, Pedro E.; Valdivieso, Nicolás; Retamal, Patricio (Austral Journal of Veterinary Sciences, 2023)
Bovine tuberculosis (bTB) is a chronic disease of animals mainly caused by Mycobacterium bovis, a zoonotic pathogen that generates economic losses in the milk and meat industry. In central Chile, the Metropolitan Region concentrates dairy herds with the highest bTB prevalence of the country and the official veterinary service has supported the evaluation of the M. bovis Bacillus Calmette-Guerin (BCG) vaccine in this area with the replacement of tuberculin purified protein derivative (PPDs) by the DIVA (Differentiating Infected from Vaccinated Animals) peptides for the bTB diagnosis in the herds. This study aimed to describe the IFN-γ response against PPDs (bovine and avian PPD) and DIVA antigenic cocktails (ESAT-6/CFP-10 and Rv3615c) in BCG vaccinated 11-month-old heifers under a natural transmission scenario. Sixty-two animals were vaccinated via subcutaneous route with a 2-8 x 105 colony forming units of BCG Russia strain and 60 control animals received sterile saline. Blood sampling was performed at time 0, previous to vaccination, and then at 3, 6, 9, 12, 15 and 18 months post-inoculation. The follow up of the IFN-γ response in animals determined that the BCG vaccination interferes with the diagnosis of bTB using the traditional bovine PPD between 9 and 12 months post-inoculation. Furthermore, the sensitization with non-tuberculous mycobacteria (NTM) was also interfering the diagnosis relying in PPDs, suggesting the need of using DIVA antigens under this epidemiological condition, whether or not the BCG vaccine is administered in cattle, in order to improve the accuracy of bTB diagnosis in central Chile.